Bioethical principles and nutrition in palliative care - Andrade, Joana S. de (2017)
The last few decades have been witness to huge advances in medical technology and, consequently, in Ethics. One area that reflects this progress has been the area of food, nutrition and hydration in Palliative Care. The current review focuses on the overall knowledge about Ethics in the field of Nutrition in Palliative Care regarding the principles of autonomy, beneficence, non-maleficence and justice.